GEOESTATÍSTICA A CARACTERIZAÇÃO DO SOLO E DA VEGETAÇÃO EM FLORESTA OMBRÓFILA MISTA - Amaral, Lúcio de Paula (2010)
The Mixed Ombrophilous Forest (MOF) is an important forest type that occurs in southern Brazil, but has been heavily exploited since the time of colonial Brazil, resulting in a large number of fragments. The characterization of these fragments is routinely performed using forest survey, without concern about the influence of spatial dependence in the behavior variables within their limits and their mapping, where geostatistics has great potential as a tool to characterize the vegetation and soil, which are the objectives of this work. The study area is located a fragment of MOF in General Carneiro, Paraná, where they were installed 45 sampling units, georeferenced, to characterize the forest and soil. Floristic survey was conducted for phytosociological analysis and estimates of biomass and carbon, soil sampling for chemical analysis and particle size, measure the depth and penetration resistance of soil, and identification of forest uses, which used the kriging for estimating the program GS +. In the forest the diversity index, dominance and evenness showed the best results, where the Shannon index was the best, and soil penetration resistance, pH (CaCl2) and soil organic matter (SOM), phosphorus (P ) and potassium (K) showed the best results, where SOM was the best. The forest appeared in disturbance system, influencing the behavior of its variables, and soil properties were very variable, resulting in high variance of the samples, which generally made it difficult to fit semivariograms. It is concluded that the methodology has achieved the objectives of the work, proving to be a tool with great potential for the understanding of forest and soil, generating information that can help in sustainable use and conservation of important natural resources.